Greek and Roman historiography in late antiquity : fourth to sixth century A.D. - Marasco, Gabriele. (Brill's Companions in Classical Studies Online I, ISBN: 9789004219274., 2003)
This book is the first comprehensive study of Greek and Latin historiography from Constantine to the end of the sixth century AD. It aims to examine the development of late antique historiography, stressing chiefly the relations between pagan and Christian historians, their polemics but also their often neglected agreements. Of special importance is the study of the Church historians who are considerable but not adequately known sources for the political and social history of the period. Greek and Latin Historiography in Late Antiquity is a highly valuable and useful reference tool for both scholars and students. Greek and Roman Historiography in Late Antiquity has been selected by Choice as Outstanding Academic Title (2005).